Alginate–lavender nanofibers with antibacterial and anti-inflammatory activity to effectively promote burn healing. Issue 9 (9th February 2016) - Hajiali, Hadi; Summa, Maria; Russo, Debora; Armirotti, Andrea; Brunetti, Virgilio; Bertorelli, Rosalia; Athanassiou, Athanassia; Mele, Elisa
Abstract : Electrospun nanofibers of alginate containing lavender essential oil with antimicrobial and anti-inflammatory properties for the treatment of UV-induced skin burns. Abstract : One of the current challenges in wound care is the development of multifunctional dressings that can both protect the wound from external agents and promote the regeneration of the new tissue. Here, we show the combined use of two naturally derived compounds, sodium alginate and lavender essential oil, for the production of bioactive nanofibrous dressings by electrospinning, and their efficacy for the treatment of skin burns induced by midrange ultraviolet radiation (UVB). We demonstrate that the engineered dressings reduce the risk of microbial infection of the burn, since they stop the growth of Staphylococcus aureus . Furthermore, they are able to control and reduce the inflammatory response that is induced in human foreskin fibroblasts by lipopolysaccharides, and in rodents by UVB exposure. In particular, we report a remarkable reduction of pro-inflammatory cytokines when fibroblasts or animals are treated with the alginate-based nanofibers. The down-regulation of cytokines production and the absence of erythema on the skin of the treated animals confirm that the here described dressings are promising as advanced biomedical devices for burn management.